2018
DOI: 10.1038/s41586-018-0199-7
|View full text |Cite
|
Sign up to set email alerts
|

EMI1 switches from being a substrate to an inhibitor of APC/CCDH1 to start the cell cycle

Abstract: Mammalian cells integrate mitogen and stress signaling prior to the end of G1 phase to decide whether or not to enter the cell cycle1–4. Before cells can replicate their DNA in S phase, they have to activate cyclin-dependent kinases (CDKs), induce an E2F transcription program, and inactivate an E3 ubiquitin ligase, the anaphase promoting complex/cyclosome (APC/CCdh1). It was recently shown that stress can return cells to quiescence after CDK2 activation and E2F induction but cannot after inactivation of APC/CC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
146
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 130 publications
(166 citation statements)
references
References 26 publications
7
146
1
Order By: Relevance
“…Inactivation of APC/C Cdh1 generally occurs late in G1 and is induced by cyclin E/CDK2 complexes, suggesting that engagement of the Rb-E2F switch should be required prior to the APC/C Cdh1 switch. Indeed, Cappell et al demonstrated that APC/C Cdh1 inactivation was observed in the vast majority of cells only after prior engagement of the Rb-E2F switch and within 1 h before S phase initiation [75]. Consistent with the idea that this mechanism confers a temporal order to the switches, E2F-dependent expression of Emi1 [77] was also shown to play a crucial role in the kinetics of APC/C Cdh1 inactivation and was required to make the switch irreversible, thus preventing reactivation of APC/C Cdh1 during S phase.…”
Section: Integration Of the Rb-e2f Switch With Other Bistable Switchesmentioning
confidence: 99%
“…Inactivation of APC/C Cdh1 generally occurs late in G1 and is induced by cyclin E/CDK2 complexes, suggesting that engagement of the Rb-E2F switch should be required prior to the APC/C Cdh1 switch. Indeed, Cappell et al demonstrated that APC/C Cdh1 inactivation was observed in the vast majority of cells only after prior engagement of the Rb-E2F switch and within 1 h before S phase initiation [75]. Consistent with the idea that this mechanism confers a temporal order to the switches, E2F-dependent expression of Emi1 [77] was also shown to play a crucial role in the kinetics of APC/C Cdh1 inactivation and was required to make the switch irreversible, thus preventing reactivation of APC/C Cdh1 during S phase.…”
Section: Integration Of the Rb-e2f Switch With Other Bistable Switchesmentioning
confidence: 99%
“…In addition, E2F‐stimulated transcription drives production of the APC/C inhibitor protein EMI1 whose levels rise through the G1/S transition (reviewed in ). EMI1 is subsequently stabilized by a variety of ubiquitination and phosphorylation events near the G1/S transition . Once APC/C is inactivated, DNA replication (i.e., S phase) is destined to begin.…”
Section: S Phase Entrymentioning
confidence: 99%
“…3e), we hypothesized that, in the presence of CDK4/6 inhibitor, full Rb phosphorylation and inactivation may occur only after APC/C CDH1 inactivation. This is possible since APC/C CDH1 inactivation can be mediated by cyclin E-CDK2 phosphorylation on CDH1 even in the absence of EMI1 12,13 . This hypothesis is further strengthened by the finding that APC/C CDH1 inactivates at approximately the same level of cyclin E/A-CDK activity in the alternate and canonical pathway (Extended Data Fig.…”
Section: The Canonical Signaling Order Of Rb Inactivation Before Apc/mentioning
confidence: 99%
“…Previous studies of the canonical pathway showed that APC/C CDH1 inactivation can be initiated either by E2F-mediated activation of cyclin E-CDK2 or expression of the APC/C CDH1 inhibitor EMI1 12,13 . However, irreversible APC/C CDH1 inactivation requires a double negative feedback between EMI1 and APC/C CDH1 (Fig.…”
Section: Apc/c Cdh1 Inactivation Is Reversible Until Rb Inactivation mentioning
confidence: 99%
See 1 more Smart Citation